Keterampilan Manajemen Waktu Pada Mahasiswa Psikologi Universitas Negeri Makassar Yang Menjalani Program Merdeka Belajar Kampus Merdeka (MBKM) BKP Proyek Kemanusiaan : Merna Karlely, Ahmad Razak, Novita Maulidya Djalal - Karlely, Merna; Razak, Ahmad; Maulidya Djalal , Novita (SOCIAL PHILANTHROPIC, 2023)
Time management is one of the skills or abilities of individuals in utilizing every available time effectively and optimally to compile an organized plan starting from the most important so that it can help individuals in achieving goals and doing all the work well and minimizing stress. The purpose of this study is to explore time management skills in MBKM BKP Humanitarian Project students. This study uses qualitative methods with a phenomenological study research approach, to see how the experience is aware and interprets the experience with an in-depth interview method. There were three respondents in this study with different backgrounds. The results of this study illustrate that the MBKM process that occurs further changes the pattern of student habits such as irregular sleep and eating hours, is required to be independent without parental assistance and interact more with many people. Time management skills possessed by students themselves are setting goals, setting priorities, making agendas or schedules and controlling good time. The impact of MBKM BKP Humanitarian Project positively brings students to be more able to interact and socialize with many and makes their thoughts more open, ideas and initiatives, while the negative impact felt is feeling tired more often and lack of rest time.